Everything you need to ace world history in one big fat notebook : the complete middle school study guide - Vengoechea, Ximena (Big fat notebook., 2016)
A workbook that examines world history on a middle school level. Organized by key concepts, the text includes mnemonic devices, definitions, timelines and doodles to help the subject stick in your brain, so you can ace your class.